Assessment of metal residues in soil and evaluate the plant accumulation in copper mine tailings of Dongchuan, Southwest China - Lijuan Deng; Min Yin; Shuanglin Yang; Xiaoyun Wang; Juan Chen; Deren Miao; Genshen Yin; Shuhua Zhai; Yuan Su; Cheng Wu; Zhen Ren (Frontiers in Plant Science)
IntroductionThis study aimed to identify suitable plants for remediating metal pollution in copper tailing soil and supporting ecological reclamation in Dongchuan, Yunnan, focusing on three major mining regions: Tangdan, Yinmin, and Lanniping.MethodsThe Nemerow comprehensive pollution index was employed to evaluate the metal contamination levels, and the enrichment and transfer capacities of the dominant plants for Cd, Cu, Pb, and Zn were analyzed to identify remediation candidates.ResultsThe findings revealed severe pollution in the copper tailing soil, with Cu as the primary pollutant, and with a pollution rate of 77.778%. A total of 96 plant species from 42 families and 87 genera were recorded, including 29 dominant species across 17 families and 26 genera, with herbs comprising 62.068% of the dominant types. Among the tested plants, Leucaena leucocephala, Rumex acetosa, Festuca rubra, and Salix balfouriana exhibited significantly higher metal enrichment and transfer capacities, rendering them for ecological restoration. Salix balfouriana with the highest comprehensive membership function score of 5.298 was identified as the preferred species for ecological restoration in the Dongchuan Cu tailing area. Correlation analysis revealed a positive relationship between the metal content in underground plant parts and both the total metal content and organic matter (OM) in the rhizosphere soil, whereas a negative correlation was observed with soil pH.DiscussionThe soil in the Dongchuan Cu tailing area is severely contaminated by metals, mainly Cu. Among the identified plants, S. balfouriana emerged as the most suitable candidate for metal accumulation. This study establishes a comprehensive theoretical framework for the application and promotion of phytoremediation technology in the Dongchuan copper tailings area.